Student academic stress reviewed from critical thinking skills - Nurwahyuni Nurwahyuni (Universitas Aisyah Pringsewu, 2023)
Academic stress is a dangerous thing if it is not managed properly, uncontrolled academic stress can trigger physiological, mental, emotional and physical consequences. One of the factors that influence academic stress is critical thinking skills. The aims of this study were (1) to identify the level of academic stress among students, (2) to identify the relationship between academic stress and critical thinking skills, and (3) to identify differences in academic stress for male and female students in terms of critical thinking skills. The subjects of this research were students of the Guidance and Counseling Education Study Program, Faculty of Education, Tadulako University, Palu. This research is a survey research. Student academic stress was measured using a scale adapted from the Perception of Academic Stress Scale (PAS). Critical thinking skills were measured using a critical thinking skills test adapted from the Critical Thinking Questionnaire (CThQ). The research data were analyzed using the Run Spearman test and one way ANOVA test with the help of SPSS statistics version 26. The results of the data analysis showed (1) the student stress level was 47.45 in the very high category. (2) There is no significant relationship between critical thinking skills and student academic stress as indicated by a significance value of 0.196 or more than 0,05. (3) There is no difference in academic stress between male and female students in terms of gender. The results of Fhitung are smaller than Ftable (0.070 less than 3.92). Abstrak: Stres akademik merupakan hal yang berbahaya jika tidak dikelola dengan baik, stres akademik yang tidak terkendali dapat memicu konsekuensi fisiologis, mental, emosional dan fisik. Salah satu faktor yang mempengaruhi stres akademik adalah kemampuan berpikir kritis. Tujuan penelitian ini adalah (1) mengidentifikasi tingkat stres akademik pada mahasiswa, (2) mengidentifikasi hubungan stres akademik dengan kemampuan berpikir kritis, dan (3) mengidentifikasi perbedaan stres akademik pada mahasiswa laki-laki dan perempuan di istilah keterampilan berpikir kritis. Subyek penelitian ini adalah mahasiswa Program Studi Pendidikan Bimbingan dan Konseling Fakultas Ilmu Pendidikan Universitas Tadulako Palu. Penelitian ini merupakan penelitian survei. Stres akademik mahasiswa diukur dengan menggunakan skala yang diadaptasi dari Skala Persepsi Stres Akademik (PAS). Kemampuan berpikir kritis diukur menggunakan tes kemampuan berpikir kritis yang diadaptasi dari Critical Thinking Questionnaire (CThQ). Data penelitian dianalisis menggunakan uji Run Spearman dan uji one way ANOVA dengan bantuan statistik SPSS versi 26. Hasil analisis data menunjukkan (1) tingkat stres mahasiswa sebesar 47,45 dengan kategori sangat tinggi. (2) Tidak terdapat hubungan yang signifikan antara kemampuan berpikir kritis dengan stres akademik mahasiswa yang ditunjukkan dengan nilai signifikansi 0,196 atau lebih dari 0,05. (3) Tidak ada perbedaan stres akademik antara mahasiswa laki-laki dan perempuan ditinjau dari jenis kelamin. Hasil Fhitung lebih kecil dari Ftabel (0,070 kurang dari 3,92).